Expression 28: "y" equals 2.5 "x" plus 1 left brace, 13.8 less than "y" less than 17 , right bracey=2.5x+113.8<y<17
28
Expression 29: "y" equals .7 "x" plus 8 left brace, 7 less than "y" less than 9.2 , right bracey=.7x+87<y<9.2
29
Expression 30: left parenthesis, "x" minus 4 , right parenthesis squared plus left parenthesis, "y" minus 11 , right parenthesis squared less than or equal to 3 squaredx−42+y−112≤32
30
Expression 31: "y" equals negative 10.5y=−10.5
negative 10.5−10.5
1010
31
Expression 32: "y" equals negative 11y=−11
negative 11−11
1111
32
Expression 33: "y" equals negative 11.5y=−11.5
negative 11.5−11.5
1010
33
Expression 34: "y" equals negative 12y=−12
negative 12−12
1010
34
Expression 35: "y" equals negative 7y=−7
negative 10−10
1010
35
Expression 36: "y" equals negative 7.5y=−7.5
negative 10−10
1010
36
Expression 37: "y" equals negative 8y=−8
negative 10−10
1010
37
Expression 38: "y" equals negative 8.5y=−8.5
negative 10−10
1010
38
Expression 39: "y" equals negative 9y=−9
negative 10−10
1010
39
Expression 40: "y" equals negative 9.5y=−9.5
negative 10−10
1010
40
Expression 41: "y" equals negative 10y=−10
negative 10−10
1010
41
Expression 42: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 3.5y=−.5·sin.6x−1+−3.5
42
Expression 43: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 3y=−.5·sin.6x−1+−3
43
Expression 44: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 2.5y=−.5·sin.6x−1+−2.5
44
Expression 45: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 2y=−.5·sin.6x−1+−2
45
Expression 46: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 1.5y=−.5·sin.6x−1+−1.5
46
Expression 47: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 1y=−.5·sin.6x−1+−1
47
Expression 48: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative .5y=−.5·sin.6x−1+−.5
48
Expression 49: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 6y=−.5·sin.6x−1+−6
49
Expression 50: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 5.5y=−.5·sin.6x−1+−5.5
50
Expression 51: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 7y=−.5·sin.6x−1+−7
51
Expression 52: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 5y=−.5·sin.6x−1+−5
52
Expression 53: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 4y=−.5·sin.6x−1+−4
53
Expression 54: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 4.5y=−.5·sin.6x−1+−4.5
54
Expression 55: "y" equals negative .5 times sine left parenthesis, .6 "x" minus 1 , right parenthesis plus negative 6.5y=−.5·sin.6x−1+−6.5